Comparative analysis of sample preparation methods to determine the concentration of arsenic in soil- and plant-samples - Várallyay, Szilvia; Szilva, Diána; Soós, Áron; Kovács, Béla (Acta Agraria Debreceniensis, 2016)
Arsenic contamination of the fields and groundwater is a global problem. Alföld is the most affected area in Hungary. Irrigation witharsenic contaminated water, and crop production on the contaminated soil can cause a food safety problem, because arsenic is easy taken up by the cell of the plant roots. To prevent this, very important to monitoring the arsenic content of soils and plants. Inductively coupled plasma mass spectrometry (ICP-MS) is a fast, easy method to determined the concentration of minerals in the case of plant and soil samples The analytical methods can give reliable, results if the analytical process, including the sample preparation method, is the best. The objective of this study was to compare 3 type of sample preparation method which was dry ashing, wet digestion in open system, and microwave digestion. As a result of our experiement shows the microwave digestion is the appropriate method to determined the arsenic content of soil samples. In the case of plant samples we can use wet digestion in open system or microwave digestion as a samle preparation method.